A Single δ9-Tetrahydrocannabinol (THC) Dose During Brain Development Affects Markers of Neurotrophy, Oxidative Stress, and Apoptosis - Philippot, Gaëtan; Forsberg, Erica; Tahan, Caroline; Viberg, Henrik; Fredriksson, Robert (Frontiers in Pharmacology, 2019)
Δ9-tetrahydrocannabinol (THC) is one of the most used drugs during pregnancy and lactation and efficiently crosses the placental and blood-brain barriers. Despite the recent legalization initiatives worldwide, the adverse outcome pathway (AOP) of THC following exposure during brain development, is incompletely understood. We have previously reported that a single injection of THC on postnatal day (PND) 10 altered adult spontaneous behavior and habituation rates in adult mice. Similar behavioral alterations have been reported following PND 10 exposure to the commonly used over-the-counter analgesic acetaminophen (AAP; also known as paracetamol); as both THC and AAP interact with the endocannabinoid system, we hypothesize that this system might be involved in the AOP of both these pharmaceuticals/drugs. Here, we report that a single THC dose on PND 10 decreased transcript levels of Trkb 24 h after exposure in both the frontal and parietal cortex, and in the hippocampus in mice. Effects on the Nrf2-Keap1 axis were also found in both the parietal cortex and hippocampus following neonatal exposure to THC. THC exposure also increased transcript levels of Cb1r in the parietal cortex and increased pro apoptotic protein BAX in the frontal cortex. This study is important for mainly 3 reasons: (1) we are starting to get information from the developmental neurotoxic AOP of THC where we suggest that transcriptional changes of the neurotrophic receptor Trkb are central, (2) our PND 10 exposure model provides information relevant to the exposures happening in humans and (3) since PND 10 exposure to AAP also decreased Trkb transcript levels, we suggest THC and AAP may share key events in their respective AOP through endocannabinoid-mediated alterations of the BDNF-TRKN signaling pathway.